The Mechanisms and the Applications of Antibacterial Polymers in Surface Modification on Medical Devices - Qiu, Haofeng; Si, Zhangyong; Luo, Yang; Feng, Peipei; Wu, Xujin; Hou, Wenjia; Zhu, Yabin; Chan-Park, Mary B.; Xu, Long; Huang, Dongmei (Frontiers in Bioengineering and Biotechnology, 2020)
Medical device contamination caused by microbial pathogens such as bacteria and fungi has posed a severe threat to the patients’ health in hospitals. Due to the increasing resistance of pathogens to antibiotics, the efficacy of traditional antibiotics treatment is gradually decreasing for the infection treatment. Therefore, it is urgent to develop new antibacterial drugs to meet clinical or civilian needs. Antibacterial polymers have attracted the interests of researchers due to their unique bactericidal mechanism and excellent antibacterial effect. This article reviews the mechanism and advantages of antimicrobial polymers and the consideration for their translation. Their applications and advances in medical device surface coating were also reviewed. The information will provide a valuable reference to design and develop antibacterial devices that are resistant to pathogenic infections.